Incidental thyroid nodules in patients with primary hyperparathyroidism. Issue 12 (11th March 2014) - Phillips, David J.; Kutler, David I.; Kuhel, William I.
Abstract Background It is desirable to detect neoplastic thyroid disease before proceeding with surgical therapy for hyperparathyroidism so that both conditions can be treated with a single operation. Methods Between March 1998 and June 2009, 227 patients with primary hyperparathyroidism were treated with surgical therapy. Of these, 217 were evaluated preoperatively with a modified 4‐dimensional CT and ultrasonography. The medical records of these patients were reviewed in order to document the incidence and significance of thyroid pathology in this cohort of patients. Results Thyroid nodules were identified in 159 of the 217 patients (73.3%). Nine of 217 patients (4.1%) were treated with either a partial or a total thyroidectomy at the time of parathyroidectomy. Three of these patients had papillary thyroid carcinoma, 1 had a Hurthle cell carcinoma, and 1 had an incidental micropapillary thyroid carcinoma. Conclusion The rate of clinically significant thyroid malignancy in patients undergoing surgical treatment of primary hyperparathyroidism was 1.8%. © 2014 Wiley Periodicals, Inc. Head Neck 36: 1763–1765, 2014